2022
DOI: 10.3390/biomedicines10081971
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of the Same Polishing Protocol on the Surface Roughness of Denture Base Acrylic Resins

Abstract: This investigation aims to determine the effect of the same polishing protocol on the surface roughness (Ra) of different resins obtained by different processing techniques. Acrylic resins obtained by CAD/CAM technology overcame the disadvantages identified in conventional materials. A total of thirty samples (six of each resin): self-cured, heat-polymerized, injection molded, CAD/CAM 3D-printed and CAD/CAM milled were prepared. JOTA® Kit 1877 DENTUR POLISH was used to polish the samples by two techniques: man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The surface roughness of dental acrylic resins is mainly affected by acrylic resins' inherent features, the polishing technique, and the operator's manual skills [1,4,6]. The authors of the present study propose a mechanical device for polishing acrylic resins, regardless of the individual operator's skills.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The surface roughness of dental acrylic resins is mainly affected by acrylic resins' inherent features, the polishing technique, and the operator's manual skills [1,4,6]. The authors of the present study propose a mechanical device for polishing acrylic resins, regardless of the individual operator's skills.…”
Section: Introductionmentioning
confidence: 84%
“…Acrylic resins are used for various applications in dentistry, such as denture base materials. The most common material used for denture base is poly (methyl methacrylate) (PMMA) [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its use as pre-formed blocks for milling is associated with lower porosity [29]. However, there is no consensus among authors on the best technique for polishing FDM PEEK or milled PMMA [21,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The surface roughness of the materials used as a denture base is a critical property and should be kept within acceptable values to avoid plaque accumulation, bacterial colonization, and staining. 16,17 Although avoiding surface roughness might be a complicated task in digital manufacturing due to the nature of the object production, 17,18 studies have found that surfaces with roughness values higher than 0.2 μm maximize the rate of bacterial colonization. 17,19,20 This roughness is a normal sequel to the layer-by-layer building of the object in 3D printing technology.…”
Section: Introductionmentioning
confidence: 99%